Big lessons from the little Akkermansia muciniphila in hepatocellular carcinoma - Yang, Yanguang; Shi, Xinli (Frontiers in Immunology, 2025)
Hepatocellular carcinoma (HCC) is the most frequently occurring type of liver tumor and is considered one of the most common primary malignant neoplasms. The prognosis for HCC is dismal because of its complicated etiology and high level of medication resistance. Immunotherapy is presently regarded as one of the most effective therapeutic options for HCC; nevertheless, because of the disturbance of intestinal flora, immunotherapy shows low antitumor efficacy. An increasing body of research indicates that intestinal flora, particularly Akkermansia muciniphila (A. muciniphila), is vital for the treatment of tumors. Studies have demonstrated that the diminished effectiveness of immunotherapy in cancer patients is associated with a reduction in A. muciniphila levels, suggesting that increasing A. muciniphila levels significantly enhance the efficacy of immunotherapy. A. muciniphila functions as a gut probiotic and can treat and prevent a wide range of illnesses, including cancer. Consequently, preserving A. muciniphila abundance is enough to prevent and lower the danger of developing cancer disorders. In this review, we critically evaluate the current body of research on A. muciniphila, with a primary focus on its biological properties and functions. The different illnesses that A. muciniphila treats were then discussed, particularly the way it works with liver cancer. This review aims to give a novel treatment plan for patients with HCC as well as a theoretical foundation for improving HCC immunotherapy.